Ancient Mitochondrial Genomes Reveal Extensive Genetic Influence of the Steppe Pastoralists in Western Xinjiang - Ning, Chao; Zheng, Hong-Xiang; Zhang, Fan; Wu, Sihao; Li, Chunxiang; Zhao, Yongbin; Xu, Yang; Wei, Dong; Wu, Yong; Gao, Shizhu; Jin, Li; Cui, Yinqiu (Frontiers in Genetics, 2021)
The population prehistory of Xinjiang has been a heat topic among geneticists, linguists, and archaeologists. Current ancient DNA studies in Xinjiang exclusively suggest an admixture model for the populations in Xinjiang since the early Bronze Age. However, almost all of these studies focused on the northern and eastern part of Xinjiang, the prehistoric demographic processes that occurred in western Xinjiang have been seldomly reported. By analyzing complete mitochondrial sequences from the Xiabandi cemetery (XBD; 3,500-3,300 BP), the up-to-date earliest cemetery excavated in western Xinjiang, we show that all the XBD mitochondrial sequences fall within two different West Eurasian mtDNA pools, indicating the migrants into western Xinjiang from west Eurasians were a consequence of the early expansion of the middle and late Bronze Age steppe pastoralists (Steppe_MLBA), admixed with the indigenous populations from Central Asia. Our study provides genetic links for an early existence of the Indo-Iranian language in southwestern Xinjiang and suggests the existence of Andronovo culture in western Xinjiang was not only by the dispersal of ideas but also including population movement.